'As foreign as it gets': indigenous immigrants, transnationality, and rage in Sherman Alexie's The Business of Fancydancing. Issue 1 (2nd January 2018) - Marciniak, Katarzyna
ABSTRACT: The article considers Sherman Alexie's directorial debut, The Business of Fancydancing (2002), as an important contribution to transnational cinema. It invites us to review our conceptions of outside/ inside, liminality, borders, and interstitiality in the light of the complicated political status of Native Americans—as (un)belonging members of dependent nations. It asks what cinematic aesthetic might be adequate to the contingent sovereignty of Native Americans. I examine the way a form of mise-en-abyme (in a story featuring a Native American poet heralded by non-Natives but rejected as 'selling out' by his own people) informs the challenges Native American filmmakers face themselves in trying to avoid the exploitation of their own culture. The analysis acknowledges how the 'redundancy' of Native Americans is given expressive form through a sonic and visual play with 'indigenous rage' and through discontinuous narrative structure. I argue that the film attests to Alexie's preparedness to risk potentially counterproductive representations of indigenous self-realization in the context of a damaging history of cultural appropriation, and explore how Fancydancing attempts to transgress borders without erecting new ones.